Ima Hogg the extraordinary cultural patron behind the unusual name - Warren, David B. 1937- (The Museum Fine Arts Houston, 2016)
"This engaging biography paints an intimate portrait of Ima Hogg (1882-1975), a philanthropist who left her mark on Texas through her dedicated support of the arts, education, and mental health"...